Z-Disk-Associated Plectin (Isoform 1d): Spatial Arrangement, Interaction Partners, and Role in Filamin C Homeostasis - Winter, Lilli; Staszewska-Daca, Ilona; Zittrich, Stefan; Elhamine, Fatiha; Zrelski, Michaela M.; Schmidt, Katy; Fischer, Irmgard; Jüngst, Christian; Schauss, Astrid; Goldmann, Wolfgang; Stehle, Robert; Wiche, Gerhard (Cells, 2023)
Plectin, a highly versatile cytolinker protein, is crucial for myofiber integrity and function. Accordingly, mutations in the human gene (PLEC) cause several rare diseases, denoted as plectinopathies, with most of them associated with progressive muscle weakness. Of several plectin isoforms expressed in skeletal muscle and the heart, P1d is the only isoform expressed exclusively in these tissues. Using high-resolution stimulated emission depletion (STED) microscopy, here we show that plectin is located within the gaps between individual α-actinin-positive Z-disks, recruiting and bridging them to desmin intermediate filaments (Ifs). Loss of plectin in myofibril bundles led to a complete loss of desmin Ifs. Loss of Z-disk-associated plectin isoform P1d led to disorganization of muscle fibers and slower relaxation of myofibrils upon mechanical strain, in line with an observed inhomogeneity of muscle ultrastructure. In addition to binding to α-actinin and thereby providing structural support, P1d forms a scaffolding platform for the chaperone-assisted selective autophagy machinery (CASA) by directly interacting with HSC70 and synpo2. In isoform-specific knockout (P1d-KO) mouse muscle and mechanically stretched plectin-deficient myoblasts, we found high levels of undigested filamin C, a bona fide substrate of CASA. Similarly, subjecting P1d-KO mice to forced swim tests led to accumulation of filamin C aggregates in myofibers, highlighting a specific role of P1d in tension-induced proteolysis activated upon high loads of physical exercise and muscle contraction.
CRIS-Team Scopus Importer:2023-05-26
Keywords: chaperone-assisted selective autophagy; cytolinker; desmin intermediate filaments; myofibril; plectin; skeletal muscle